A new species of robber fly of the genus Leptogaster Meigen, 1803 (Diptera: Asilidae) from Dagestan, Russia - D.M. Astakhov (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2019)
A new species Leptogaster rutulica sp. n. from southwestern Dagestan is described with comprehensive photographs of the external morphology and details of the male genitalia. Differences from other species of the genus Leptogaster Meigen, 1803, and especially from the closely related species L.  subtilis Loew, 1847 are shown. The species is characterized by the presence of very characteristic features, which are not observed in other members of Leptogaster species occurring in the Caucasus. The new species differs from L. armeniaca Paramonov, 1930, L. calceata Engel, 1925, L. cylindrica (De Geer, 1776) and L. pubicornis Loew, 1847 in the shape of the epandrium with a distinct spine medioposteriorly, by the presence of numerous black hairs and strong bristles at the tip of the epandrium, and the lateral processes of gonostyli sharply curved and bent down. The new species has two extensive apubescent areas on the mesoscutum, reaching the middle of the mesonotum and also clearly distinguished from Leptogaster subtilis by the presence of the distinct spine medio-posteriorly on the epandrium